ACTUAL DISCOURE ABOUT TIPES FND DEVELOPMENT TENDENCIES NATIONAL STATE - E. G. Ponomareva (Vestnik MGIMO-Universiteta)
The processes of globalization have determined significant changes in the prerogatives of nation states. In the twenty-first century the state no longer acts as a sole subject having a monopoly of integrating the interests of large social communities and representing them on the world stage. An ever increasing role in the global political process is played by transnational and supranational participants. However, despite the uncertainty and ambiguity of the ways of the development of the modern world, it can be argued that in the foreseeable future it is the states that will maintain the role of the main actors in world politics and bear the responsibility for global security and development. All this naturally makes urgent the issues related to the search for optimal models of nation state development. The article analyzes approaches to understanding patterns, problems and prospects of the development of this institution existing in modern political science. These include the concept of "dimensionality" based on the parameters of scale (the size of the territory) of the states and their functions in the international systems, as well as the "political order". In the latter case the paper analyzes four models: the nation-state, statenation, consociation, quasi-state. The author's position consists in the substantiation of the close dependence of the success of a model of the state on its inner nature, i.e. statehood. On the basis of the elaborated approach the author understands statehood as "the result of historical, economic, political and foreign policy activity of a particular society in order to create a relatively rigid political framework that provides spatial, institutional and functional unity, that is, the condition of the society’s own state, national political system." Thus statehood acts as a qualitative feature of the state.